Synthesis and characterization of Fe3O4-PEG-LAC-chitosan-PEI nanoparticle as a survivin siRNA delivery system. (March 2017) - Arami, S; Rashidi, MR; Mahdavi, M; Fathi, M; Entezami, AA
The limited effectiveness of the conventional methods for cancer treatment makes the researchers to find novel safe and effective therapeutic strategies. One of these strategies is to use small interfering RNAs (siRNAs). A major challenge here is the siRNA delivery into the cells. The purpose of this study was to design and prepare a biocompatible, biodegradable, and safe nanosized particle for siRNA delivery into human breast cancer MCF-7 and leukemia K562 cells. Chemically synthesized magnetic nanoparticles containing polyethyleneglycol-lactate polymer (PEG-LAC), chitosan, and polyethyleneimine (PEI) were successfully prepared and used as a gene delivery vehicle. The nanoparticles were characterized by Fourier transform infrared spectroscopy and zeta potential. The Fe3 O4 -PEG-LAC-chitosan-PEI nanoparticle showed efficient and stable survivin siRNA loading in gel retardation assay. The cytotoxicity of the prepared nanoparticle was studied using 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2H-tetrazolium bromide assay and was compared with that of mitoxantrone (MTX) in combination with the prepared siRNA delivery system to evaluate the possible synergic effect of MTX and survivin siRNA. The nanoparticles with and without noncomplementary siRNA showed low toxicity against both cell lines; however, a twofold decrease was observed in cell survival percent after MTX addition to MCF-7 cells treated with either nanoparticle itself or complexed with noncomplementary siRNA. While survivin siRNA nanoplex caused threefold decrease in the cell survival percent, its combination with MTX did not result in a significant increase in the cytotoxic effect. Therefore, Fe3 O4 -PEG-LAC-chitosan-PEI nanoparticle should be considered as a potential carrier for enhanced survivin siRNA delivery into MCF-7 and K562 cells.